Chronic hemorrhagic pseudocyst following crural hernioplasty (Revista Argentina de Cirugía, 2021)
Among the long term complications of hernioplasty, chronic hemorrhagic pseudocyst has not been reported so far in our country. Complementary imaging methods for diagnosis are described and surgical resection is highlighted as the definitive treatment. It is concluded that this complication as well as inguinodynia and hernia recurrence influence the degree of postoperative satisfaction.
Keywords: chronic pseudocyst; hernioplasty